2009
DOI: 10.1007/s00296-009-1056-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment guidelines in two primary care populations with gout

Abstract: Published guidelines for the treatment of gout aim to improve the evidenced-based management of this disorder. Unfortunately, several studies suggest that these guidelines are not routinely followed in clinical practice. Limited data exist comparing different groups of primary care providers regarding compliance with published gout guidelines. We conducted a retrospective study comparing two different general internal medicine (IM) practices and evaluated compliance with these guidelines. All patients with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…The low adherence of primary care physicians to published evidence-based treatment guidelines for the diagnosis and management of gout57 undoubtedly reflects inadequate dissemination of these guidelines. Contributing factors may include the lack of involvement of GPs in guideline development, publication of guidelines only in specialist rheumatology journals (even though GPs are the main target audience) and the absence of financial incentives to audit and improve standards of care.…”
Section: Doctors’ Knowledge Of Gout and Their Approach To Treatmentmentioning
confidence: 99%
“…The low adherence of primary care physicians to published evidence-based treatment guidelines for the diagnosis and management of gout57 undoubtedly reflects inadequate dissemination of these guidelines. Contributing factors may include the lack of involvement of GPs in guideline development, publication of guidelines only in specialist rheumatology journals (even though GPs are the main target audience) and the absence of financial incentives to audit and improve standards of care.…”
Section: Doctors’ Knowledge Of Gout and Their Approach To Treatmentmentioning
confidence: 99%
“…There is also evidence of nonspecialist physicians prescribing inappropriate drugs for gout, which prove ineffective in the long term [12]. Compliance with gout treatment guidelines in primary care is reportedly poor, with limited numbers of patients achieving the target of serum uric acid levels <0.36 mmol/l as a consequence [13]. Physicians are also frequently unaware of their gout patients' poor compliance due to inadequate communications, and patient compliance would probably benefit if patients had more information and a closer interaction with their care providers [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, Wall et al showed in their study that in primary care settings, where most gout patients are treated, serum urate is monitored yearly in only one-quarter of patients 15. Other studies have shown that fewer than 50% of patients met the goal urate level within 6 months or were flare free within 12 months 16,17.…”
Section: Gaps In Quality Of Carementioning
confidence: 99%